2021
DOI: 10.5603/gp.a2021.0007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of epidural analgesia on maternal-neonatal outcomes: a retrospective study

Abstract: This article is available in open access under Creative Common Attribution-Non-Commercial-No Derivatives 4.0 International (CC BY-NC-ND 4.0) license, allowing to download articles and share them with others as long as they credit the authors and the publisher, but without permission to change them in any way or use them commercially.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…al. [22] any adverse outcomes of child and mother were found significant. The longer hospital stay was also observed in a study of Yin and Hu [23], and was probably related to increased rate of maternal intrapartum fever.…”
Section: Discussionmentioning
confidence: 86%
“…al. [22] any adverse outcomes of child and mother were found significant. The longer hospital stay was also observed in a study of Yin and Hu [23], and was probably related to increased rate of maternal intrapartum fever.…”
Section: Discussionmentioning
confidence: 86%
“…Ballesteros-Meseguer et al (2016) and Shmueli et al (2017) also showed a tendency to perform an episiotomy in women who received epidural anesthesia [ 31 , 32 ]. In contrast, in a study by Liu et al (2021), no significant correlations were found between epidural anesthesia and the frequency of episiotomy [ 33 ].…”
Section: Discussionmentioning
confidence: 86%
“…Epidural labor analgesia (ELA) is widely used. Although it can greatly reduce maternal labor pain, studies have found that ELA drugs affect the normal reflex arc of urination, weaken the contraction of abdominal muscles and the diaphragm, cause urination and bladder pain, as well as postpartum urinary retention [ 1 , 2 , 3 , 4 , 5 ]. Direct bladder catheterization is the solution to urinary retention during and after delivery.…”
Section: Introductionmentioning
confidence: 99%